Dairy farmers' decision‐making to implement biosecurity measures: A study of psychosocial factors. Issue 2 (2nd November 2019) - Moya, Sebastián; Tirado, Francisco; Espluga, Josep; Ciaravino, Giovanna; Armengol, Ramon; Diéguez, Javier; Yus, Eduardo; Benavides, Bibiana; Casal, Jordi; Allepuz, Alberto
Abstract: Biosecurity measures are a set of management procedures that prevent the risk of introducing and spreading infectious diseases to a farm, although these measures are rarely implemented in dairy farms. There are some studies that have identified that the decision to implement biosecurity measures can be influenced by several psychosocial factors (attitudes and behaviours). Thus, the objective of this study was to examine the psychosocial factors (and their interactions) influencing the implementation of biosecurity measures in dairy farms in Spain, through the views of dairy farmers and veterinarians from Catalonia (northeast Spain) and Galicia (northwest Spain). Face‐to‐face in‐depth interviews were performed with 16 dairy farmers (nine from Catalonia and seven from Galicia) and 16 veterinarians (eight from Catalonia and eight from Galicia). Grounded theory analysis was performed on the transcripts, following the subtopics of: information sources, individual factors of the farmer, social dynamics, official veterinary services and other factors. The study identified the importance of veterinarians as a source of information, including their communication skills, the individual experiences of farmers, traditions of the farms and availability of time and space in the dairy farmer's decisions making. Further, it suggests the need to deepen the knowledge of the farm workers and the obligatory biosecurity measures. This research represents a starting point to develop future strategies to improve the implementation of biosecurity measures in dairy farms.